2019
DOI: 10.1111/psyp.13429
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive accuracy is related to long‐term stress via self‐regulation

Abstract: Interoception describes the ability to perceive internal bodily signals. Previous research found a relationship between interoceptive accuracy (IAcc) and cardiovascular outcomes during or after acute stress. So far, the association between IAcc and long‐term stress has not been investigated, although this would be important to identify a starting point to prevent long‐term stress. To address this idea in the current study, we examined the relationship between IAcc and long‐term stress, which was assessed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 116 publications
(161 reference statements)
0
16
0
Order By: Relevance
“…Speculating about the neurophysiological level, the anterior insula region, and the dorsomedial prefrontal cortex might underlie both interoceptive abilities [ 5 , 91 , 92 ] as well as sensory processing during mindfulness practice [ 93 , 94 ] and, could, therefore, act as an interface region activated via the yoga session. Furthermore, previous studies showed that high IAc was related to better self-regulation [ 26 , 95 , 96 , 97 , 98 ]. At the same time, yoga can enhance self-regulation, exemplarily, via increased meta-awareness and, more generally, integrated top-down and bottom-up mechanisms for self-regulation [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Speculating about the neurophysiological level, the anterior insula region, and the dorsomedial prefrontal cortex might underlie both interoceptive abilities [ 5 , 91 , 92 ] as well as sensory processing during mindfulness practice [ 93 , 94 ] and, could, therefore, act as an interface region activated via the yoga session. Furthermore, previous studies showed that high IAc was related to better self-regulation [ 26 , 95 , 96 , 97 , 98 ]. At the same time, yoga can enhance self-regulation, exemplarily, via increased meta-awareness and, more generally, integrated top-down and bottom-up mechanisms for self-regulation [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…These inconsistent findings might result from methodological differences between the studies, such as various instructions. Moreover, associations between interoceptive abilities and stress were found (e.g., Schulz and Vögele, 2015 ; Maeda et al, 2019 ; Schultchen et al, 2019a ; Schulz et al, 2020 ; Opdensteinen et al, 2021 ). Furthermore, decreased interoceptive abilities have been assumed to play a role in the perception of somatic symptoms ( van den Bergh et al, 2017 , 2019 ).…”
Section: Introductionmentioning
confidence: 97%
“…There is only one study on the relationship between long-term stress and interoception, reporting a positive relationship of r = .34 between IAcc in an HCT and dehydroepiandrosterone concentrations (DHEA) derived from hair, in a student population (Schultchen et al, 2019). DHEA is an HPA axis hormone that may antagonize cortisol effects (Blauer et al, 1991; Jogems-Kosterman et al, 2007).…”
Section: Abnormal Interoception In Stress-associated Mental Disordersmentioning
confidence: 99%
“…DHEA is an HPA axis hormone that may antagonize cortisol effects (Blauer et al, 1991; Jogems-Kosterman et al, 2007). Furthermore, negative correlations (−.28 ≤ r ≤ −.19) between questionnaire scales of chronic stress and IAcc have been reported (Schultchen et al, 2019). This pattern is in line with a single finding in a previous study showing a negative correlation of r = −.35 between the social strain scale of chronic stress and IAcc in the HCT (Schulz, Lass-Hennemann, et al, 2013).…”
Section: Abnormal Interoception In Stress-associated Mental Disordersmentioning
confidence: 99%